META-ANALISIS DETERMINAN PERDARAHAN POSTPARTUM - Fury Indah; Evi Hasnita; Nurdin Nurdin (Universitas Fort De Kock, 2023)
Postpartum haemorrhage is the most common cause of all deaths from obstetric haemorrhage. Postpartum haemorrhage is bleeding that exceeds 500 ml after the baby is born in vaginal delivery and exceeds 1000 ml in cesarean section or bleeding that is more than normal which has caused changes in vital signs. The purpose of this study was to determine the determinants of postpartum hemorrhage from national and international research publications with meta-analyses. Identify study articles by searching through Pubmed, Springer Link, Google Scholar database searches on the internet. Assessment of the quality of the studies included in this study were selected in advance, the selected journals were publication journals that were relevant to the research question, original research (original), indexed Scopus Q1, Q2, Q3, Q4 and indexed Sinta (S1, S2). The research study used was an observational cohort, case-control and cross-sectional design study. Statistical analysis using the fixed effect model or random effect model to see the estimated specific effect and the combined determinants of postpartum hemorrhage and sensitivity test to see the stability of the variables to changes. Data analysis software uses RevMan 5.4. The results showed that there were 13 countries out of 20 selected journals, the estimation of the determinant effect of Postpartum Hemorrhage in Asia from the meta analysis obtained age had an OR of 2.52 (95% CI: 1.83-3.47). Parity has an OR of 2.54 (95% CI: 1.22-5.31). Anemia has an OR of 3.43 (95% CI: 1.65-7.11). History of childbirth has an OR of 3.40 (95% CI: 2.62-4.42). Stress has an OR of 2.06 (95% CI: 0.46-9.31). Education has an OR of 1.27 (95% CI: 0.23-6.94). Lifestyle has an OR of 1.48 (95% CI: 0.85-2.22). It was concluded that the determinant of postpartum hemorrhage in Asia was anemia with the highest OR of 3.43. It is hoped that this can be used as a guideline for stakeholders in the health sector in determining program priorities to prevent and control postpartum hemorrhage problems. The results of the research can directly provide knowledge to the public about the determinants of postpartum hemorrhage and how to manage pressure to control and avoid postpartum hemorrhage